Potassium disturbance associated with an inpatient childhood asthma pathway. Issue 8 (12th October 2019) - Hung, Jonathan; Kraft, Timothy; Seefried, Brent; Johnson, David W; Bailey, Michelle; Dersch-Mills, Deonne
Abstract: Background: Paediatric asthma exacerbations in Alberta are treated via standardized order sets known as the Alberta Acute Childhood Asthma Pathway (ACAP). This pathway is utilized in paediatric tertiary hospitals and in remote and rural locations. Incidence, magnitude, and risk factors for hypokalemia in inpatients receiving salbutamol for asthma exacerbations via this pathway are presently unknown. Objective: Establish incidence, magnitude, and risk factors for hypokalemia associated with salbutamol therapy as directed by a paediatric asthma pathway. Methods: Retrospective cohort study using visit-level electronic medical data. Inpatients aged <18 years old receiving salbutamol via the ACAP with at least one potassium level were included. Hypokalemia was defined as mild (3.0 ≤ [K + ] < 3.5 mEq/L), moderate (2.5 ≤ [K + ] < 3.0 mEq/L), or severe ([K + ] < 2.5 mEq/L), as measured in serum or blood gas. Binomial logistic regression was utilized to examine risk factors for hypokalemia, route of administration, location of lowest [K + ], nil per os (NPO) status during admission, potassium supplementation, gender, and age. Results: There were 821 patients screened for analysis and 433 patients were analyzed after exclusions. There was an incidence of hypokalemia of 38.8%. Of patients experiencing hypokalemia, 71.4% were mild, 25.6% moderate, and 3.0% severe. Risk factors included nebulized salbutamol, patient location (emergency department or paediatric intensive care unit), and age (>5 years) although these risk factors may actually represent patients receiving higher doses of salbutamol. Conclusions: The majority of the 38.8% of children experiencing hypokalemia associated with the ACAP were mild. Routine monitoring of potassium status in children receiving salbutamol per standardized pathway is recommended for children with described risk factors, and ideally within the first 12 hours of presentation.